Proceedings of the 4th International Conference of Fluid Flow, Heat and Mass Transfer (FFHMT'17) 2017
DOI: 10.11159/ffhmt17.110
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Bell Nozzles

Abstract: -A Bell type nozzle is most commonly used shape for rocket nozzles. This type of nozzle not only offers significant advantages in terms of size and performance over the conical nozzle but also reduces complexity compared to annular nozzles. The nozzle uses the stagnation temperature (To) and stagnation pressure (Po) generated in the combustion chamber to create thrust by accelerating the combustion gases to a high supersonic velocity. The nozzle expansion ratio was governed by the exit velocity. During flight,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The fluid domain with boundary conditions of the bell nozzle [50] By altering the proposed second-order diffusion solution, it is possible to arrive at a much simpler but also more limited solution to the nozzle heat-transfer issue. The aerodynamic flow in electric rotor bell systems is comparable to naturally occurring rotating annular flow.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The fluid domain with boundary conditions of the bell nozzle [50] By altering the proposed second-order diffusion solution, it is possible to arrive at a much simpler but also more limited solution to the nozzle heat-transfer issue. The aerodynamic flow in electric rotor bell systems is comparable to naturally occurring rotating annular flow.…”
Section: Figurementioning
confidence: 99%
“…The nozzle shape is separated into zones and boundary conditions. For the conservation equations, the second-order upwind technique was applied, and grid adaptation was employed to precisely capture flow discontinuities [50].…”
Section: Figurementioning
confidence: 99%
“…This would lead to a supersonic expansion within the divergent section designed previously. The convergent section was produced through the application of Rao method [11]. This approach gained great success as it is the result of numerous experimental investigations.…”
Section: B Subsonic Section Designmentioning
confidence: 99%
“…In 1999, Östlund [4] tested four turbulence models that based onk ω two equations and found that only the Menter's SST model was able to capture the correct type of separation during startup and shutdown, but the wall pressure downstream of the separation was significantly different from the experimental data. Baloni et al [5] used the SST -k ω turbulence model to conduct a two-dimensional steady state simulation of a bell-shaped nozzle. The numerical simulation results and analysis results are in terms of shock structure, shock position, normal shock and asymmetric lambda shock size have good consistency.…”
Section: Introductionmentioning
confidence: 99%